Schistosomiasis in European travelers and migrants: analysis of 14 years TropNet Surveillance Data - Lingscheid, Tilman; Jänisch, Thomas (The American journal of tropical medicine and hygiene, 2017)
Schistosomiasis remains one of the most prevalent parasitic diseases worldwide and the infection is frequently found in travelers and migrants. The European Network for Tropical Medicine and Travel Health conducted a sentinel surveillance study on imported schistosomiasis between 1997 and 2010. This report summarizes epidemiological and clinical data from 1,465 cases of imported schistosomiasis. Direct pathogen detection and serology were the main diagnostic tools applied. Of these, 486 (33%) cases were identified among European travelers, 231 (16%) among long-term expatriates, and 748 (51%) among non-European immigrants. Overall, only 18.6% of travelers had received pretravel advice; 95% of infections were acquired in the African region. On species level, Schistosoma mansoni was identified in 570 (39%) and Schistosoma haematobium in 318 (22%) cases; 57.5% of patients were symptomatic. Acute symptoms were reported in 27% of patients leading to earlier presentation within 3 months. Praziquantel was used in all patients to treat schistosomiasis. Many infections were detected in asymptomatic patients. In 47.4% of asymptomatic patients infection was detected by microscopy and in 39% by serology or antigen testing. Schistosomiasis remains a frequent infection in travelers and migrants to Europe. Travelers should be made aware of the risk of schistosomiasis infection when traveling to sub-Saharan Africa. Posttravel consultations particularly for returning expatriates are useful given the high potential for detecting asymptomatic infections.
Gesehen am 08.10.2018